Photosensitizer-Gold Nanorod Composite for Targeted Multimodal Therapy** - Wang, Jian (2013)
In this work, a DNA inter-strand replacement strategy for therapeutic activity has been successfully designed for multimodal therapy. In this multimodal therapy, chlorin e6 (Ce6) photosensitizer molecules are used for photodynamic therapy (PDT), while aptamer-AuNRs, are used for selective binding to target cancer cells and for photothermal therapy (PTT) with near infrared (NIR) laser irradiation. Aptamer Sgc8, which specifically targets leukemia T cells, is conjugated to an AuNR by a thiol-Au covalent bond. and then hybridized with a Ce6-labeled photosensitizer/reporter to form a DNA double helix. When target cancer cells are absent, Ce6 is quenched and shows no PDT effect. However, when target cancer cells are present, the aptamer changes structure to release Ce6 to produce singlet oxygen for PDT upon light irradiation. Importantly, by combining photosensitizer and photothermal agents, PTT/PDT dual therapy supplies a more effective therapeutic outcome than either therapeutic modality alone.